Assessing, quantifying and valuing the ecosystem services of coastal lagoons - Newton, Alice (2020)
The natural conservation of coastal lagoons is important not only for their ecological importance, but alsobecause of the valuable ecosystem services they provide for human welfare and wellbeing. Coastal lagoons areshallow semi-enclosed systems that support important habitats such as wetlands, mangroves, salt-marshes andseagrass meadows, as well as a rich biodiversity. Coastal lagoons are also complex social-ecological systems withecosystem services that provide livelihoods, wellbeing and welfare to humans. This study assessed, quantifiedand valued the ecosystem services of 32 coastal lagoons. The mainfindings of the study are: (i) the definitions ofecosystem services are still not generally accepted; (ii) the quantification of ecosystem services is made in manydifferent ways, using different units; (iii) the evaluation in monetary terms of some ecosystem service is pro-blematic, often relying on non-monetary evaluation methods; (iv) when ecosystem services are valued inmonetary terms, this may represent very different human benefits; and, (v) different aspects of climate change,including increasing temperature, sea-level rise and changes in rainfall patterns threaten the valuable ecosystemservices of coastal lagoons.